THE DETERMINANS OF NET PROFIT MARGIN: STUDY AT PT. INDOFOOD SUKSES MAKMUR TBK. - Andriani, R. Neneng Rina; Hermansyah, Iwan; Dermawan, Wildan Dwi (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2025)
The purpose of this study is to analyse the determinants of net profit margin at Indofood Sukses Makmur Tbk Limited Company. Another goal is to analyse how the effect of Working Capital Turnover, Currents Ratio, Total Assets Turnover in the company and its effect on Net Profit Margin. The research method uses a descriptive quantitative approach with secondary data in the form of the company's annual financial statements for 2011 - 2022. The analysis tool used is multiple regression analysis. The descriptive research results show that the variables studied fluctuated during the study period. Furthermore, the simultaneous test shows that Working Capital Turnover, Turrent Ratio, and Total Asset Turnover simultaneously affect Net Profit Margin. Partial tests show that Working Capital Turnover has a positive effect on Net Profit Margin. While Current Ratio, and Total Assets Turnover have no effect on Net Profit Margin.